2021
DOI: 10.1002/aqc.3691
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional macroinvertebrate diversity of high‐altitude ponds in the Macun Cirque, Switzerland

Abstract: 1. Global environmental change is threatening freshwater biodiversity with ecological impacts predicted to be particularly severe in high-altitude regions.Despite this, an ecological understanding of high-altitude pond networks remains patchy, with only limited knowledge of the environmental and spatial predictors of taxonomic and functional diversity. Moreover, previous studies of pond ecosystems have focused primarily on taxonomic richness and largely overlooked functional diversity.2. This study examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Alpha, β, and γ diversity measures are relevant to understand metacommunity structure and the underlying processes modulating it. Many studies have analysed the β diversity of aquatic active communities, concluding that turnover is the main factor driving differences in spatial (between pond) β diversity (Atkinson et al, 2021; Fernández‐Aláez et al, 2020; Hill et al, 2021; Korhonen et al, 2010; Martins et al, 2019), but other studies have found nestedness as the main factor driving β diversity (Florencio et al, 2011; Gleason & Rooney, 2018; Pires et al, 2017). Only a few studies have assessed the β diversity of the egg bank, and they found turnover to be the main component driving β diversity (Declerck et al, 2011; Freiry et al, 2016; Freiry, Weber, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha, β, and γ diversity measures are relevant to understand metacommunity structure and the underlying processes modulating it. Many studies have analysed the β diversity of aquatic active communities, concluding that turnover is the main factor driving differences in spatial (between pond) β diversity (Atkinson et al, 2021; Fernández‐Aláez et al, 2020; Hill et al, 2021; Korhonen et al, 2010; Martins et al, 2019), but other studies have found nestedness as the main factor driving β diversity (Florencio et al, 2011; Gleason & Rooney, 2018; Pires et al, 2017). Only a few studies have assessed the β diversity of the egg bank, and they found turnover to be the main component driving β diversity (Declerck et al, 2011; Freiry et al, 2016; Freiry, Weber, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%